2014
DOI: 10.1371/journal.pone.0086254
|View full text |Cite|
|
Sign up to set email alerts
|

Altered Response Hierarchy and Increased T-Cell Breadth upon HIV-1 Conserved Element DNA Vaccination in Macaques

Abstract: HIV sequence diversity and potential decoy epitopes are hurdles in the development of an effective AIDS vaccine. A DNA vaccine candidate comprising of highly conserved p24gag elements (CE) induced robust immunity in all 10 vaccinated macaques, whereas full-length gag DNA vaccination elicited responses to these conserved elements in only 5 of 11 animals, targeting fewer CE per animal. Importantly, boosting CE-primed macaques with DNA expressing full-length p55gag increased both magnitude of CE responses and bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 62 publications
9
90
0
Order By: Relevance
“…In agreement with previous results, 20 , 21 , 76 , 77 priming with CE DNA was more efficient at inducing CE-specific T cell responses in the blood than immunization with the FL vaccine, for both Gag and Env. Gag CE-specific responses were also found in rectal mucosa lymphocytes (Env responses were not evaluated in the rectal mucosa due to sample limitations).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with previous results, 20 , 21 , 76 , 77 priming with CE DNA was more efficient at inducing CE-specific T cell responses in the blood than immunization with the FL vaccine, for both Gag and Env. Gag CE-specific responses were also found in rectal mucosa lymphocytes (Env responses were not evaluated in the rectal mucosa due to sample limitations).…”
Section: Discussionsupporting
confidence: 92%
“…We previously reported the generation of two DNA vaccines targeting the highly conserved sequences in HIV Gag 20 , 21 , 73 (and its homolog SIV p27CE) 76 and in HIV Env (Env CE) 77 ( Figure 1 A) and demonstrated induction of robust CE-specific T cell responses in cohorts of vaccinated macaques. The CE selection included analysis of MHC binding prediction to address immunogenicity in humans, and we found that epitopes from all MHC class I known supertypes were represented in Gag CE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations